THE DEVELOPMENT MODEL OF INDEX CARD MATCH TO INCREASE THE LEARNING OUTCOMES OF 4TH GRADE STUDENTS ON SOCAL SCIENCES AT ELEMENTARY SCHOOL - Sri Rohartati; Eri Subekti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. The background of this research was the low learning outcomes of students in Social Sciences (IPS). This research aims to obtain information about improving learning outcomes in Social Sciences (IPS) subject by applying the Index Card Match method in elementary school. This research was held at SDN Mandalawangi, Cipatat Sub-district,  West Bandung District using a quasi-experimental method with the Nonequivalent Control Group Design. The subject of this research was the 4th grade students of SDN Mandalawangi, Cipatat Sub-district,  West Bandung District. There were 60 students that divided into 2 classes, class IV A and IV B. The research sample was taken using saturated sampling technique because the number of samples was equal to the population. The techniques of data analysis include normality test, homogeneity test and t-test. After getting the pre-test and post-test learning outcomes of both classes students, the score were analyzed until the final results stated by the difference average test. The score for control class was 8.4 and the average score for the experimental class was 34.6. Based on the results, the application of the Index Card Match method can improve student learning outcomes in social sciences subject in elementary school and the hypothesis that said there is a significant improvement in student learning outcomes by applying the Index Card Match method on social sciences subject in elementary school is acceptable. Keywords : learning outcomes, index card match method